Results of a three-year follow-up and quality of life dynamics after pulmonary thromboendarterectomy - A. S. Klinkova; O. V. Kamenskaya; I. Yu. Loginova; A. M. Chernyavsky; A. G. Edemsky; D. V. Khabarov; V. V. Lomivorotov (Российский кардиологический журнал)
Aim. To evaluate the results of a three-year follow-up of patients with chronic thromboembolic pulmonary hypertension (CTEPH) and quality of life (QOL) dynamics after pulmonary thromboendarterectomy (PTE).Material and methods. The study included 125 patients with CTEPH aged 49,7± 11,9 years. Three-year follow-up included the recording of adverse cardiovascular events, surgeries, death during the period from the end of hospitalization and up to three years. The SF-36 questionnaire was used to assess physical and mental wellbeing before and three years after PTE. Multivariate linear regression was used to assess the factors affecting QOL in the long-term postoperative period.Results. During a three-year follow-up, adverse cardiovascular events was recorded in 1,9% of patients. One patient underwent coronary artery bypass graft surgery and one patient — cholecystectomy. Reoperative PTE was not carried out. The overall three-year survival rate was 90,4%.At baseline, patients with CTEPH had a low level of physical and mental well-being (<40 points). Three years after the operation, these parameters significantly increased (p<0,05), but did not exceed 50 points. Multivariate linear regression revealed an unfavorable effect of early postoperative residual pulmonary hypertension on the physical health three years after PTE. Other factors (age, sex, body weight, comorbidity, hospital acquired complications) did not affect the physical and emotional aspects of QOL.Conclusion. Three-year survival rate in patients with CTEPH after PTE was 90,4%. During the follow-up period, no recurrent thromboembolic events were recorded. Adverse cardiovascular events were recorded in 1,9% of patients. Three years after surgery, the physical and mental health increased in comparison with preoperative values, but did not exceed 50 points on the SF-36 questionnaire. The physical aspect of QOL after surgery is affected by early postoperative residual pulmonary hypertension.